MODEL IDENTIFIKASI SISTEM KEBOCORAN/PEMBOROSAN ANGGARAN PEMERINTAH KABUPATEN/KOTA PROVINSI SUMATERA UTARA - Sari, Ayu Kurnia; Saputra, Hendra; Chrisna, Heriyati (Seminar Nasional Sosial Sains dan Teknologi Halal, 2022)
The research aims to identify budget leakage/waste that occurs in the District/City Government of North Sumatra Province, and implement a system model of budget leakage/waste. The main problem to be investigated is identifying indicators of budget leakage/wasting of the North Sumatran regency/municipal government budget which is seen from the size of the deficit in the APBD, the amount of regional expenditure carried out, namely direct spending and indirect spending. From these indicators, budget leakage will be identified and then a model for implementing the budget leakage/waste system will be made based on the theory of cost control, so that it can directly identify the budget that is suspected to be leaking/wasteful in its use. So that the government can continue to save on the use of the budget so that it does not harm the people and the state continuously. The analytical model used in identifying budget leakage/waste using the Panel Auto Regression Distribution Lag (ARDL) model and in implementing the budget leakage/wasting system model using the Vector Autoregression (VAR) model. ARDL which is used to find out the indicators of budget leakage/waste will then determine the cause of the leakage. Furthermore, by using the Vector Autoregression (VAR) model, it is possible to apply a budget leakage/wasting system model in the regencies/municipalities of the province of North Sumatra. So that it has a significant impact in minimizing leakage/waste of local government budget s.ARDL results can identify and determine the effect of budget leakage/waste that has a high chance of leading to acts of corruption or irregularities in implementing the APBD budget for both direct and indirect expenditures. Later it will be seen how the synchronization between the budget and the realization of the expenditure budget used by the district/city government of North Sumatra province in implementing the APBD for 1 year will be seen. From the results, it can be seen that what is used using the Auto Regression Distribution Lag Panel Model can be seen below. That the probability is 0.00 means that in this model there is no budget leakage that occurred in 5 regencies/cities of North Sumatra Province including the city of Medan, Kab. Deli Serdang, Mandailing Regency and North Tapanuli Regency